PENGARUH PENGETAHUAN PERPAJAKAN, SOSIALISASI PERPAJAKAN, PENERAPAN SISTEM E-FILING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI MASA PANDEMI COVID-19 - Tasum, Tasum (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The purpose of this study was to determine the effect of the variable knowledge of taxation, tax socialization, and the application of the e-filing system on individual taxpayer compliance during the Covid-19 pandemic. This research uses associative quantitative method using a questionnaire with a semantic differential measurement scale. This research was conducted on individual taxpayers who are registered as mandatory SPT and have NPWP at KPP Pratama Pondok Gede.